2018
DOI: 10.1128/aem.02894-17
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Probing for Microbial Iron Reduction in Chocolate Pots Hot Spring, Yellowstone National Park

Abstract: Chocolate Pots hot springs (CP) is a circumneutral-pH Fe-rich geothermal feature located in Yellowstone National Park. Previous Fe(III)-reducing enrichment culture studies with CP sediments identified close relatives of known dissimilatory Fe(III)-reducing bacterial (FeRB) taxa, including and However, the abundances and activities of such organisms in the native microbial community are unknown. Here, we used stable isotope probing experiments combined with 16S rRNA gene amplicon and shotgun metagenomic sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Raw sequences were processed using QIIME following the protocol for 454 pyrosequencing data or Illumina MiSeq 16S rRNA gene amplicon sequencing data, according to previously published methods (Fortney et al, 2016 , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raw sequences were processed using QIIME following the protocol for 454 pyrosequencing data or Illumina MiSeq 16S rRNA gene amplicon sequencing data, according to previously published methods (Fortney et al, 2016 , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…mtoABCD ; Rhodobacter ferrooxidans, foxEZY ; and Rhodopseudomonas palustris, pioABC ; Ilbert and Bonnefoy, 2013 , and references therein) using command-line BLAST and the BLASTp function in IMG. Genes coding for putative EET systems, which are not homologous to known models, were identified according to previously published methods (Fortney et al, 2018 ). MAGs encoding putative outer-membrane porins, and multiheme c- type cytochromes ( c- cyts) with predicted extracellular and periplasmic locations, as well as other supplemental genes predicted to be involved in Fe transformation pathways, are hereafter referred to as pcc -like EET systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iron (hydr)oxide mats that form at Chocolate Pots (pH 5.8 to 6.0 at source), a vapor influenced mildly acidic spring just south of Norris Geyser Basin (Allen and Day 1935), is perhaps the most well studied iron (hydr)oxide mat in a hot spring in YNP if not the world. This spring has been studied extensively from both the mineralogical [e.g., (Wade et al 1999;Wu et al 2013)] and the biological perspectives [e.g., (Fortney et al 2016;Fortney et al 2018a;Fortney et al 2018b;Pierson and Parenteau 2000;Trouwborst et al 2007)]. Current understanding suggests that Fe(II) in the source vent waters of Chocolate Pots is rapidly oxidized by O2 that is in supersaturating concentrations due to the activity of oxygenic Cyanobacteria.…”
Section: Geological Controls On the Distribution Of Redox Active Minementioning
confidence: 99%
“…Homologs of putative porin-cytochrome complexes, which have been hypothesized to be involved in EET and iron reduction in Geobacter (Liu et al 2014), have been identified in iron oxide mats recovered from Chocolate Pots hot spring in YNP (Fortney et al 2016;Fortney et al 2018a;Fortney et al 2018b). These homologs were related to divergent Ignavibacterium-and Thermodesulfovibrio-like populations, among others.…”
Section: Mechanism Of Fe Reduction During Microbial Metabolismmentioning
confidence: 99%